Mixed Abilities and Varied Experiences: A group autoethnography of a virtual summer internship - Mack, Kelly; Das, Maitraye; Jain, Dhruv; Bragg, Danielle; Tang, John; Begel, Andrew; Beneteau, Erin; Davis, Josh Urban; Glasser, Abraham; Park, Joon Sung; Potluri, Venkatesh (ASSETS: The 23rd International ACM SIGACCESS Conference on Computers and Accessibility, 2021)
The COVID-19 pandemic forced many people to convert their daily work lives to a “virtual” format where everyone connected remotely from their home. In this new, virtual environment, accessibility barriers changed, in some respects for the better (e.g., more flexibility) and in other aspects, for the worse (e.g., problems including American Sign Language interpreters over video calls). Microsoft Research held its first cohort of all virtual interns in 2020. We the authors, full time and intern members and affiliates of the Ability Team, a research team focused on accessibility, reflect on our virtual work experiences as a team consisting of members with a variety of abilities, positions, and seniority during the summer intern season. Through our autoethnographic method, we provide a nuanced view into the experiences of a mixed-ability, virtual team, and how the virtual setting affected the team’s accessibility. We then reflect on these experiences, noting the successful strategies we used to promote access and the areas in which we could have further improved access. Finally, we present guidelines for future virtual mixed-ability teams looking to improve access.